Countering Terrorist and Extremist Criminal Offences: A Situational Approach - Lakbayev, Kanat; Nurgaliyev, Bakhyt; Khanov, Talgat; Bashirov, Aleksander; Smatlayev, Baurzhan (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
The study examines the unique characteristics of terrorist and extremist activities in Kazakhstan compared to other countries. The primary objective is to analyze public perceptions of extremism and terrorism while identifying key socioeconomic and political factors contributing to their emergence. A quantitative survey method involving 2,905 respondents assessed public attitudes toward these issues. Additionally, a situational approach was used alongside historical and comparative legal methods to trace the development of extremism in Central Asia and highlight distinctive regional influences. The survey findings indicate that declining living standards, internal political instability, and external factors significantly contribute to extremist activities. Based on these insights, the study proposes targeted recommendations, including strengthening the legal framework, enhancing inter-agency coordination, integrating advanced information technologies, and adopting a situational approach to mitigate extremist threats. These measures are expected to improve national security and facilitate international cooperation in combating terrorism. The study underscores the necessity of a comprehensive and proactive strategy to address the region's evolving nature of extremist threats.